The role of Sharia compliance, Good Corporate Governance, Competence on SUMUT zakat management - Nasution, Akmal Huda; Siregar, Tapi Rumondang Sari; Rahman, Haikal; Putra, Hendra Kurnia (Universitas Siliwangi, 2023)
Introduction to The Problem: Zakat, a core Islamic practice, mandates Muslims to give to needy people. Indonesia's sizable Muslim population and Islamic financial institutions create substantial zakat potential. However, effective collection and distribution face hurdles, including a lack of understanding, trust, and optimal management. Legislation and education efforts aim to improve zakat management, with transparency and good governance crucial. Enhancing public awareness and accountability can unlock the full potential of zakat funds for social welfare.Purpose/Objective Study: This study aims to analyze the effect of Sharia compliance, Good Corporate Governance, and Amil Zakat competence on zakat management in North Sumatra Province.Design/Methodology/Approach: The population of this study is all Amil Zakat in North Sumatra Province, while the sample is all managers of the Institution of Zakat in North Sumatra Province which are under the auspices of the National Board of Zakat Republic of Indonesia (BAZNAS) of North Sumatra Province. Data were collected through a questionnaire instrument and analyzed using descriptive statistical analysis techniques and Structural Equation Model (SEM) analysis.Findings: The results of the study show that Sharia compliance has a positive and significant influence on the management of zakat. The implementation of Good Corporate Governance (GCG) in zakat management institutions also has a positive impact on zakat fund collection, good reputation, and transparency and accountability in the distribution of zakat funds. As well as amil competence also has a positive and significant influence on the management of zakat. The results of the study also emphasize the importance of Sharia compliance, the implementation of Good Corporate Governance, and increasing the competence of amil in zakat management. To improve zakat management, zakat institutions, government and society need to work together to ensure fair, transparent and competitive zakat management.